(untitled) (Journal of Interdisciplinary Insights, 2024)
Driven by the continuous progress of society and the development of humanities, the trend of integration of art and culture has become increasingly obvious, and its influence is particularly prominent in various fields, especially the art of singing. Young singing artists have suddenly emerged on the stage, and they have shown significant progress and innovation in the integration of singing and performance. With the gradual growth of people’s understanding and demand for the fields of art and singing, TV singing competitions frequently appear in the public eye and are warmly welcomed by the masses. Since the reform and opening up, my country’s exchanges and interactions with the world have become more frequent, and the opportunities for exchanges and visits have also increased significantly. A large number of outstanding scholars went overseas for further studies and introduced rich scientific knowledge and cultural achievements. In the field of vocal music, singing methods and performance skills have been further improved and improved. In the field of vocal art performance, the integration of singing skills and performance skills is particularly close. They are like the unity of body and soul, and play a vital role in singing performance. This kind of integration can not only touch the emotional depth of the audience and lead the flow of the audience’s emotions, but also have a profound impact on the psychological state of the audience. Therefore, in vocal artistic interpretation, expressiveness is an indispensable component. The success or failure of the seamless connection between singing and performance depends on the joint action of many factors, including but not limited to key elements such as musical perception, artistic accomplishment, personal traits, insight, perception and presentation. The interpretation of music is the re-creation of the original music work, which requires the performer not only to have a profound artistic background, but also to have a deep understanding of the artistic style of the work, so that he can perfectly reproduce the music in the music performance and make it show a unique aesthetic value. Music creation is presented to the audience in its rich and colorful interpretation process. Only when the singer not only shapes and displays its unique artistic characteristics, but also can convey the emotional depth and emotional depth inherent in the work in an extremely delicate and accurate way. Only by understanding the values ​​and cultural meanings can the audience truly feel the infinite charm of music and enjoy that outstanding and indescribable aesthetic experience. In view of the significant and non-negligible differences between the artistic attributes contained in the musical work itself and the singer’s personal style characteristics, different singers’ interpretations of the same musical work will inevitably show obvious performance differences. The difference is not only reflected in the style of interpretation, but also in the grasp and conveying of the emotions of the works. Therefore, music singers need to master and present their unique artistic characteristics in an extremely precise way. Through in-depth analysis and re-creation of musical works, they need to highlight the uniqueness of the works and the art emanating from the performance process. Beauty, thus making every performance an audio-visual feast, allowing the audience to feel fresh shock and profound artistic enjoyment in every experience. With the continuous deepening of educational reform, the educational concepts of music performance majors are also constantly updated. The comprehensive implementation of innovative educational reforms in the music performance major can inject new ideas and methods into the development of the major, allowing students majoring in music performance to keep up with the times. In this way, we can cultivate a large number of outstanding music performance talents with keen thinking and excellent practical ability for the society, thereby further promoting the sustainable development of the music performance profession.